Granulocyte Colony Stimulating Factor (G-CSF) Induced Splenic Infarction in Breast Cancer Patient Treated with Dose-Dense Chemotherapy Regimen - Majed A. Alshamrani; Meteb Al-Foheidi; Ahmed H. Abdulrahim (Case Reports in Oncological Medicine)
Introduction. Granulocyte colony-stimulating factor (G-CSF) is commonly used for prevention and treatment of febrile neutropenia among solid tumor patients. It is considered an effective and relatively safe supportive care medication; however, it can cause rare and serious side effects such as spleen rupture or infarction. Case Presentation. We are reporting a case of a 27-year-old female with breast cancer who has been treated with dose-dense chemotherapy and received colony-stimulating factor as primary prevention of febrile neutropenia that was complicated halfway through with splenic infarction. This finding was confirmed by computed tomography (CT) scan and splenic biopsy. Management was conservative without the need of surgical intervention. Conclusion. Although splenic infarction is an extremely rare side effect of G-CSF, it can be a serious complication that should be recognized, monitored, and managed carefully.